TERM PREGNANCY: PREVALENCE, ETIOLOGY AND PATHOGENESIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
It is no secret that today, due to the daily increase in the number of children born after the due date, according to the recommendations of the International Federation of Gynecologists and Obstetricians (FIGO) and the American College of Obstetricians and Gynecologists (ACOG), a pregnancy lasting 42 weeks or more is considered to be a postterm pregnancy (PTG). In local obstetrics, a pregnancy lasting more than 287 days is considered to be postterm, which ends with a biologically premature birth [18, 22,24].